A crossover study comparing in-plane and out-of-plane approaches for simulated ultrasound-guided central venous cannulation on phantom models by anaesthesiology trainees - Yap, KB; T, Shereen SP; Yeoh, CN; Liu, CY; Nadia MN; O, Joanna SM (Pusat Perubatan Universiti Kebangsaan Malaysia, 2019)
This prospective crossover study compared the incidence of posterior vessel wall puncture between two approaches during ultrasound-guided simulated central venous cannulation by anaesthesiology trainees. Each phantom model, simulating a central vein and artery, was cannulated by 37 anaesthesiology trainees under ultrasound-guidance using the in-plane approach (IPA) and out-of-plane approach (OPA). Total procedural time and the time taken from starting image scanning until commencing puncture, was recorded. The number of attempts required to achieve successful venous cannulation was noted. Finally, the models were examined for posterior venous wall and arterial puncture. Total procedural time was shorter with the OPA (26.5 vs 50.3 seconds, p=0.001). The time taken from starting image scanning until commencing puncture was shorter for the OPA (2.2 vs 12.3 seconds, p<0.0001). The IPA resulted in significantly more attempts for cannulation. Twenty and eleven participants were successful within the first pass using the OPA and IPA, respectively (p=0.034). There was no difference in the incidence of posterior vessel wall puncture between these two techniques. The OPA resulted in less arterial puncture compared to the IPA (2 vs 9, p=0.022). The incidence of posterior vessel wall puncture between the IPA and OPA during ultrasound-guided simulated central venous cannulation by anaesthesiology trainees was comparable.